2021
DOI: 10.1111/evj.13486
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural features of subchondral radiolucent lesions in the medial femoral condyle of juvenile Thoroughbreds: A microcomputed tomography and histological analysis

Abstract: Background:The aetiology of equine medial femoral condyle (MFC) subchondral bone radiolucencies (SR) is unknown.Objectives: Characterise the microstructural structural features of MFC SR in juvenile Thoroughbreds with microcomputed tomography (μCT) and histology.Study design: Cross-sectional post-mortem study.Methods: Distal femurs were collected at post-mortem. Conventional tomodensitometry was employed to scout for MFCs with and without SR lesions (SR+ and SR−, respectively). Group 1 were CT MFC SR+ and Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Equine subchondral bone radiolucent lesions (SRs) or cysts are most frequently located in the cranial medial femoral condyle (MFC) 1‐3 . Survey radiographs prior to the selection of Thoroughbred yearling sales have revealed a radiographic prevalence of 3.4%‐7.8% of Thoroughbred yearlings afflicted with MFC SR 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Equine subchondral bone radiolucent lesions (SRs) or cysts are most frequently located in the cranial medial femoral condyle (MFC) 1‐3 . Survey radiographs prior to the selection of Thoroughbred yearling sales have revealed a radiographic prevalence of 3.4%‐7.8% of Thoroughbred yearlings afflicted with MFC SR 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been observed that SRs in foals aged 6 months or less are first located axially in the MFC 1,2 . The youngest foal reported in the literature with histology of a naturally occurring axial MFC SR is 5 weeks of age 1 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations